Determinants of asset-backed securitized firm's performance - Dabas, Nurayati (2018)
Asset-backed securities are a financial techniques that allow firms to quickly earn cash. Not long after asset-backed securities first emerged in the United States in 1970, it became the most mainstream financing component for all firms in the United States. The practice then began to spreads widely around the world, especially in Malaysia. However at the end of 2007, the United States faced the subprime mortgage crisis and the crisis affected several countries. This situation did not affect Malaysia until the end of 2008 when asset-backed securities stalled and then began to fall because investors had become more cautious in making any investments which also affected securitized firms. Before this current study was conducted, it was not very certain exactly what factors impact the performance of securitized firms in Malaysia. Based on a review of the literature, this research proposed a model to test the factors that can impact the performance of securitized firms in Malaysia; to investigate relationship between factors securitized firms in Malaysia; and to examine their effect on securitized firm’s performance. Therefore, the Corporate Debt Pricing model were tested and revalidated in this research to understand and to measure the performance of securitized firms in Malaysia. This study consist of three models, the first model is internal factors based on Corporate Debt Pricing model such as Asset, Liquidity and Leverage. These factors have a great impact on the securitized firm's performance. However based on previous researchers, external factors also had high impact to increase securitized firm's performance such as Overnight Policy Rate (OPR) and Inflation. External factors can impact the ability of a business or investment to achieve its strategic goals and objectives. Combination of internal and external factors as second and third models is applied to improve and develop model to increase securitized firm’s performance in Malaysia. The panel data study extracted from the Rating Agency Malaysia report, Securitization Commission Malaysia and financial reports. This study analysed 436 observations and 91 tranches in Malaysia from 2004 to 2016. The data were analysed using STATA through Multivariate Panel Regression Analysis (MPRA) by the pooled Ordinary Least Square (OLS), and Fixed Effects Model (FEM) and Random Effects Model (REM) were used as estimation methods. However, based on Hausman Test, this study analyses the model using FEM and 4 out of the 5 hypothesized relationship were supported. The results indicated, firm’s total assets (ASSET) showing strong, positive and significance relationships with the firm's performance. Besides that, asset factors highly influencing firm securitized performance in Malaysia following by leverage, Overnight Policy Rate and inflation. However, this study found the liquidity is not significance in this study.